Air Pollution Control Engineering Air Pollution Control Engineering - Lawrence K. Wang, PhD, PE, DEE
Air Quality and Pollution Control; Fabric Filtration; Cyclones; Electrostatic Precipitation; Wet and Dry Scrubbin; Condensation; Flare Process; Thermal Oxidation; Catalytic Oxidation; Gas-Phase Activated Carbon Adsorption; Gas-Phase Biofiltration; Emerging Air Pollution Control Technologies;